Rethinking intoxicated sexual encounters. (2nd January 2023) - Bogren, Alexandra; Hunt, Geoffrey; Petersen, Margit Anne
Abstract: Social research on alcohol and sexual encounters has tended to be siloed into several different research endeavors, each addressing separate aspects of wanted and unwanted sexual encounters. While sociologists have focused on the patterns of social interaction, status competition, and emotional hierarchies of sexual encounters, they have left the role of alcohol intoxication largely unexamined. Conversely, the two dominant approaches to sexual encounters within alcohol research, the theories of alcohol myopia and alcohol expectancy, while focusing on alcohol have tended to take little account of the socio-relational dynamics and gendered meanings involved in those encounters. Our aim in this theoretical paper is to begin to bring together some of the concepts from these different research strands in examining how the social processes of intoxication potentially impact heteronormative sexual scripts and hence notions of femininity and masculinity among cisgender, heterosexual women and men. Our discussion is focused on the concepts of ritual and scripts; power, status, and hierarchies; and socio-spatial contexts, which are central to an understanding of the gendered and embodied social practices that take place within intoxicated sexual events; the emotional nature of the socio-spatial contexts within which they occur; and the socio-structural conditions that frame these events.